PERAWATAN MESIN PERSIAPAN BAHAN BAKU (FINIR) INDUSTRI KAYU LAPIS PT. HARJOHN TIMBER LTD, PROVINSI KALIMANTAN BARAT - Mondina, Resta Rene; Hidayat, Imam (Universitas Tanjungpura, 2025)
The condition of the machine is one of the important factors that affect the preparation process of plywood raw materials. The decline in engine performance and low engine productivity are the main causes of the company's declining productivity in producing plywood. This study aims to analyze the type of machine maintenance of the plywood industry at the stage of preparation of raw materials. The methods used in this study are observation and interviews to obtain information about the functions and components of the machine, the type of maintenance, the frequency of maintenance, and the maintenance of the machine at the stage of preparation of raw materials (veneer). The results of the study show that in the process of making veneer, most types of maintenance are classified as unplanned maintenance, except at the rotary stage. Components such as rotary knives, ganggi, kibiki blades, nose bar, and knife pad are included in the category of planned maintenance with maintenance frequencies every two hours. Maintenance actions involve maintenance in accordance with the repair procedures listed in the company's SOP